Pengaruh Penambahan Fiber Pada Tanah Terhadap Nilai CBR - Novelia Yuni Pangarungan; Meti; Lintje Tammu Tangdialla (Paulus Civil Engineering Journal, 2023)
One alternative to stabilize the soil is mixing fiber with soil. This study aims to determine the effect of adding fiber to the soil on the CBR value. The land was taken from the Tambasa road area, Tamalanrea District, Makassar City. Then, feature testing and compaction testing (standard proctor) were carried out to obtain optimum water content and after that proceed to CBR (Unsoaked design) testing. The results showed that the characteristics of the soil including clay and CBR testing on both samples obtained CBR values ​​increased with the addition of 0.5% fiber and decreased with the addition of 0.75% and 1% fiber. From the research results, it is known that the more fiber added to the soil, the CBR value will decrease.